Financial reporting material misstatements, earnings conservatism and managerial replacement decisions - Jo Ting Wei (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: Based on signal theory and legitimacy theory, this paper examines whether firms with financial reporting misstatements (restatements) would prefer conservative financial reporting to send signals regarding their determinants of improving financial reporting credibility and legitimate organizational image in Taiwan. This paper further examines whether these firms reduce the demand for conservative financial reporting after replacing managers in the reveal of restatements. Design/methodology/approach: This paper adopts the ordinary least squares (OLS) regression models to estimate the hypotheses and uses different measures of earnings conservatism, such as the Basu's (1997) asymmetric timeliness of earnings measure based on a one-year period and the Basu's (1997) asymmetric timeliness of earnings measure based on a multi-year period. Finding: The results show that financial reporting behavior of restating firms would become more conservative in the reveal of restatements. However, when restating firms make replacement decisions for managers following restatements, they would demand less conservative financial reporting. This suggests that earnings conservatism and corporate governance may be substitutes in the context of restatements in Taiwan. Research limitations/implications: The findings have essential implications for Taiwanese security regulators and those who are debating the value of earnings conservatism for capital markets. When Taiwanese security regulators make regulations in relation to corporate governance and financial reporting, they must consider how to encourage firms to strengthen corporate governance and financial reporting credibility. Furthermore, to some extent, the findings of this paper support the efforts made by security regulators to enhance manager turnover disclosure transparency. Originality/value: By extending and advancing past research on restatements and earnings conservatism, this paper contributes to support that restating firms would enhance earnings conservatism following restatements in Taiwan. Moreover, this paper also contributes to support that earnings conservatism may be the substitute of governance mechanisms such as manager replacement in the context of restatements in Taiwan. Due to different institutional backgrounds and governance strength between Western countries and Asian countries, it's important to examine what post-restatement actions would be taken by Taiwanese firms and how they select optimal governance structure in the reveal of restatements. The findings of this paper facilitate to enhance the understanding of the relationship between restatements and earnings conservatism and how corporate governance affects the above relationship following restatements in Taiwan.
Keywords: M41; M43; M49; 330; Misstatement Disclosure; Financial Reporting Credibility; Earnings Conservatism; Manager Replacement